EFFECTIVENESS OF MRSA DETECTION METHODS IN THE LABORATORY PRACTICE - A BRIEF REVIEW - Neli M. Ermenlieva; Tatina T. Todorova; Gabriela S. Tsankova; Tsvetelina K. Popova; Emilia P. Georgieva (Peytchinski Publishing, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) are bacteria, responsible for severe and hard-to-manage infections in human. They are resistant to beta-lactam antibiotics - penicillins (methicillin, dicloxacillin, nafcillin, and oxacillin), cephalosporins and carbapenems, but can also be resistant to the new-generation MRSA-active cephalosporins (such as ceftaroline) or other groups of antibiotics, including aminoglycosides, macrolides, clindamycin, amphenicols, quinolones and tetracyclines. MRSA bacteria are pandemic and are often isolated in medical practice and nosocomial infections. The MRSA detection is a challenge to any clinical microbiology laboratory and demands implementation of strict protocols for active screening. While more expensive molecular techniques have the potential of offering highly sensitive and rapid results, the cultural methods require longer time but can achieve a comparable sensitivity for lower price.